APLIKASI PENGADAAN LANGSUNG AKTIVA DIBIAYAKAN BERBASIS WEB LOCAL - Rachmat Hidayat - AMIK BSI Tangerang (Evolusi : Jurnal Sains dan Manajemen, 2014)
Abstract Data processing is done by hand so felt less provide the effectiveness and efficiency of work as required in today's world. Direct Procurement Information System-based assets expensed online is a new system with the support of information technology to overcome the weaknesses in the procurement system lagsung expensed assets manually. This is necessary for PT. Angkasa Pura II (Persero) as the field of business management services and airport affairs air traffic service that promotes aviation safety and customer satisfaction. Keywords: Assets Expensed, Web Applications, Direct Procurement, Information Systems.